Sistem Pengendalian Jemuran Otomatis berbasis IoT dengan Logika Fuzzy untuk Pengkondisian Cuaca - Syarif Hidayatulloh; Joko Aryanto (Jurnal Pendidikan Informatika (EDUMATIC), 2023)
Household activities such as doing laundry are routine tasks carried out by people on a daily basis. Many individuals often leave their clothes out to dry all day due to their busy work schedules outside the home. To ensure that clothing remains unaffected by unexpected weather changes, there is a need for a device capable of automatically managing the laundry based on weather conditions. The research aims to develop an automated system for maintaining laundry based on weather conditions with the goal of enhancing efficiency and convenience in daily household activities. The methodology employed for designing this device follows the waterfall method. The testing of this device involves several hardware components, including the ESP-32 microcontroller, the DHT22 sensor for measuring air temperature, the LDR sensor for assessing light intensity in the surroundings, the rain sensor for detecting roof wetness, the MG996R servo motor for roof control, and an Android smartphone serving as the user interface display. The ultimate outcome of this research is a device capable of real-time weather detection by utilizing fuzzy logic to derive conclusions from data collected by three sensors. The weather conclusion generated is then employed as a command for opening or closing the laundry area roof, ensuring protection from rainy weather. Users receive notifications via the Android application for any changes in the roof's condition and can access weather change records.